(untitled) (Research, Society and Development, 2021)
A representative cross-sectional study was conducted to assess the knowledge about toxoplasmosis prevention, transmission routes, clinical features, and who can be infected among students from seven teaching areas of the State University of Maringá, Southern Brazil, using a self-administrated questionnaire. A total of 600 students participated in the study, 86 students did not answer or did not know about toxoplasmosis (14.3%), the other 514 (86.2%) had some information about toxoplasmosis and answered the questionnaires and most of them are unaware of the routes of transmission and prevention of this zoonosis. Less than 50% considered correct the options "do not feed cats with raw meat" (39.9%), "eat only well-cooked meats" (40.1%), and "ingest only filtered or boiled water" (42.6%). Also, misconceptions about prevention were identified when statements such as "doing fecal exams regularly" were considered correct by 20.0% of participants. Students’ average of correct answers in the health and biological areas was statistically higher than in other areas. The agricultural sciences area had the worst performance. In conclusion, there is a critical need for effective educational programs to increase the population’s awareness of toxoplasmosis since correct preventive practices are critical to control and reduce one disease’s infection without definitive treatment.